A Late devonian reef tract on northeastern Banks Island, N.W.T. - Embry, Ashton F. (Ashton Fox) (University of Calgary, 1970)
Bibliography: p. 116-118. The exposed Upper Devonian succession on northeastern Banks Island, N.W.T. is 3700 feet thick and has been correlated with the Griper Bay Formation. It consists mainly of terrigenous elastic rocks which were deposited in a marine shelf to coastal complex environment. The source area was located to the west. The age of the exposed section ranges from the base of the Frasnian to the Middle Famennian. Devonian strata have been moderately deformed,and north-south trending folds and normal faults are present. Deformation occurred during the Mississippian,and the structures were reactivated in the Tertiary. A 200 foot carbonate unit occurs in the middle of the succession . It has been herein named the Mercy Bay Member and is of Middle Frasnian age. It contains many organic buildups and represents a Devonian reef tract. The reef tract was located on the western shelf of an exogeosyncline which extended along the margin of North America between the stable craton and a western tectonic highland. The main facies changes in the Mercy Bay Member occur in an east-west direction. The organic buildups in the eastern part of the study area, which is the seaward edge of the reef tract, are narrow, linear bioherms which trend north-south. They are encased in younger terrigenous elastic rocks. To the west, the organic buildups, which are biohermal in the lower part and biostromal in the upper part, are more numerous. The lower bioherms trend east-west, and the inter-biohermal strata, which consist of dark, fine -grained, argillaceous limestones, are penecontemporaneous. The organic buildups on the western edge of the outcrop area are larger and are biohermal. The shoreward edge of the reef tract is not exposed. The lower portion of all the organic buildups is composed of corals and tabular stromatoporoids which built biogenetic banks in the quiet and intermediate energy zones. These energy zones are postulated to have been below 30 feet of water depth. The upper portion is composed of massive ...